Counseling of pregnancy danger signs and associated factors among pregnant mothers in Ethiopia: Study based on Ethiopian mini demographic and health survey, 2019 - Girma Teferi Mengistu; Bizunesh Kefale Mengistu (Elsevier, 2024)
Background: Maternal health care services utilization is low in Ethiopia, with an antenatal care service coverage of 74 %. Pregnant women who do not know pregnancy danger signs delay seeking care. This study aimed to assess counseling of pregnancy danger signs and associated factors among pregnant mothers in Ethiopia. Methods: The study was cross-sectional using the Ethiopian Mini Demographic and Health Survey 2019 data. In this study, we included a weighted sample of 2922 women. We conducted descriptive and logistic regression analysis using statistical software, SPSS version 23. Results: Only 56.6 % of pregnant mothers received counseling on pregnancy danger signs. Counseling was affected by secondary education [AOR = 1.50, 95 %CI (1.13, 1.99)], higher education [AOR = 2.36,95 %CI (1.60, 3.50)], rich [AOR = 1.53, 95 %CI (1.20, 1.95)], middle wealth [AOR = 1.33, 95 %CI (1.06, 1.67)], media [AOR = 1.23, 95 %CI (1.01, 1.50)], not pregnant [AOR = 1.27, 95 %CI (0.99, 1.63)], four + antenatal care [AOR = 1.52, 95 %CI (1.29, 1.80)], antenatal care at health posts [AOR = 1.38, 95 %CI (1.10, 1.74)], antenatal care by midwifery [AOR = 1.30,95 %CI (1.07, 1.58)], blood pressure measured [AOR = 1.76,95 %CI (1.30, 2.38)], blood sample taken [AOR = 1.73,95 %CI (1.31, 2.28)], urine sample taken [AOR = 1.44, 95 %CI (1.12, 1.86)], iron supplemented [AOR = 1.92,95 %CI (1.59, 2.33)]. Conclusions: Nearly one-half of the pregnant mothers received counseling on pregnancy danger signs. Counseling was affected by education, wealth, media, pregnancy, antenatal care related, and services provided. The antenatal care providers should be trained and guideline should be provided.